The development of reusable online learning resources for instructional design students based on the principles of learning objects - Al-Shehri, Abdullah Mohammed (Kansas State University, 2004)
The purpose of this research and development study was to design, develop, evaluate and revise reusable online learning resources based on the principles of learning objects that would support instructional design students' learning and performance in the context of ATC in Saudi Arabia. Using a research and development model (Borg and Gall, 1989), Instructional Design reusable online learning resources (ID-RORs) were iteratively and collaboratively developed and revised based on feedback gathered through formative evaluation. Between each round of qualitative formative evaluation, the ID-RORs were revised based on analysis of the data. Seven main research and development phases were carried out: research and information collecting, a needs assessment, prototype development, expert evaluations, redesign, target user evaluations and redesign. The formative evaluation of ID-RORs consisted of three phases. The first evaluation group was comprised of four experts. The purpose of this evaluation was to conduct a needs assessment. The second phase, which used feedback from two experts and two instructional design teachers, was the expert evaluation. The purpose of this evaluation was to examine the validity of the ID-RORs. The third phase, based on feedback from 11 students, was the user evaluation. The purpose of this evaluation was to examine the practicality of the ID-RORs. The overall results of the needs assessment evaluation showed that the ID-RORs prototype met an important need at ATC. The overall result of the expert evaluation showed that the ID-RORs prototype were valid for the context of ATC. Finally, the result of target user evaluation showed that the ID-RORs as revised with expert and user input were practical for the intended target users. Based on the results of this R & D study, it was concluded that the answer to the research question is yes, it is possible to develop the ID-RORs to meet the specifications of the needs assessment. The characteristics of ID-RORs are very similar to the characteristics of successful (valid and practical) reusable online resources. The final version of the ID-RORs were found to be needed, valid and practical, in the context of ATC.
Keywords: Research and development; Reusable resources; Online learning; Instructional design; Learning objects; Metadata; Education, Curriculum and Instruction (0727)Education, Technology (0710)